Efficiency, safety, and reliability analysis of turbocharging in a large container vessel. (20th January 2022) - Anantharaman, Mohan; Islam, Rabiul; Garaniya, Vikram; Khan, Faisal
Abstract: Commercial shipping is currently dominated by mega container vessels. The shipping industry has seen a 10‐fold increase in the size of containers over the last four decades. These vessels are propelled by large marine diesel engines, hereafter referred to as the main engine. The performance of the main engine is determined by its subsystems. An important part of the main engine is the turbocharging system, which contributes to its safety, efficiency, and reliability. In this study, the effectiveness and reliability of the turbocharging system are evaluated. The Australian Maritime College has a Kongsberg Engine Simulator that can produce a variety of malfunctions on a running engine's turbocharging system. Analyzing the results obtained from the simulator determines the efficiency of the turbochargers. The study will provide recommendations for improving the safety of the turbocharging system for better performance to be achieved by the turbochargers, leading to an improvement in the main engine's performance. Last, the reliability of the turbocharging system is evaluated quantitatively using a fault tree analysis and reliability block diagrams. This will enable an optimum maintenance strategy to be established to ensure the safe operation of the vessel.